Evaluation of the Effect of Platelet-Rich Plasma on Temporomandibular Joint Disorders: A Split-Match Randomized Clinical Trial - M Sezavar; Sh Shafaei Fard; H Sharifzadeh; R Pahlevan; A Badkoobeh (Islamic Azad University, 2020)
Background and Aim: The reduction of temporomandibular joint disorders (TMD) is one of the most significant concerns in dentistry. In contrast to initial treatments, such as pharmacotherapy and physiotherapy, which act as temporary tranquilizers, growth factors have shown promising results in the stimulation of cell division. Given the limited research on the positive impact of platelet-rich plasma (PRP) on the permanent treatment of joint disorders in the knee and the temporomandibular joint (TMJ), we sought to investigate the effect of PRP on TMD. Materials and Methods: Twenty patients (40 sides) presenting with TMD from 2011-2016 were included in this split-mouth clinical trial. TMD was documented by evaluating pain, limitation in movement, joint sounds, and deviation of the mandible during mouth opening. Next, 0.6 ml of PRP prepared from subjects' blood was injected into the joints. Patients were followed-up 2, 4, and 6 months postoperatively. The severity of pain was evaluated using Mann-U-Whitney test. The other criteria were analyzed using chi-square test at the follow-up sessions and McNemarchr('39')s test within each group. Results: The analysis of the results showed no difference between the two groups at the two-month follow-up. The pain intensity reduced significantly at 4- and 6-month follow-ups (P<0.05). Limitation in movement and joint sounds decreased from the second- to the sixth-month follow-up (P<0.05 and <0.02). The treatment seemed to have no impact on mandibular deviation (P<0.9). Conclusion: Treatment with PRP seems to be a favorable adjunct in several criteria of TMD.